Hubungan Terpaan Iklan Tokopedia dan Intensitas Word of Mouth pada Tokopedia Waktu Indonesia Belanja dengan Keputusan Pembelian Melalui Tokopedia - Renata Alma Ratu Nabila; Adi Nugroho; Joyo Nur Suryanto Gono (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Tokopedia launched a marketing promotion strategy in the form of the #SelaluAdaSelalubisa campaign which has been running since 2020. In this campaign, Tokopedia held a monthly promo, namely Waktu Indonesia Belanja. Two forms of marketing promotion strategies used by Tokopedia are advertising and also using word of mouth. However, in reality, Tokopedia's ranking has actually declined and according to several surveys, Tokopedia is not the preferred e-commerce for most consumers. This study uses the theory of Advertising Exposure and Elaboration Likelihood with the sampling technique of non-probability sampling. The sample is 60 people with female or male characteristics, aged 18-34 years who have been exposed to Tokopedia advertisements and have received information about Tokopedia Waktu Indonesia Belanja in the last three months. Tests in this study using the Kendall Tau_b correlation test. The results of the study show that the correlation among Tokopedia advertising exposure and the purchasing decisions has a significance value of 0.323, which means that it is not significant. Furthermore, the intensity of word of mouth with the purchasing decisions has a significance value of 0.06 which can be interpreted as significant with a correlation value of 0.302 which means it has a weak closeness and has a positive correlation direction.